Obligate Ligation-Gated Recombination (ObLiGaRe): Custom-designed nuclease-mediated targeted integration through nonhomologous end joining - Maresca, Marcello; Lin, Victor Guosheng; Guo, Ning; Yang, Yi (Genome Research, 2013)
Custom-designed nucleases (CDNs) greatly facilitate genetic engineering by generating a targeted DNA double-strand break (DSB) in the genome. Once a DSB is created, specific modifications can be introduced around the breakage site during its repair by two major DNA damage repair (DDR) mechanisms: the dominant but error-prone nonhomologous end joining (NHEJ) pathway, and the less-frequent but precise homologous recombination (HR) pathway. Here we describe ObLiGaRe, a new method for site-specific gene insertions that uses the efficient NHEJ pathway and acts independently of HR. This method is applicable with both zinc finger nucleases (ZFNs) and Tale nucleases (TALENs), and has enabled us to insert a 15-kb inducible gene expression cassette at a defined locus in human cell lines. In addition, our experiments have revealed the previously underestimated error-free nature of NHEJ and provided new tools to further characterize this pathway under physiological and pathological conditions.